An introduction to game studies : games in culture - Mäyrä, Frans (Sage Publications, 2008)
An Introduction to Game Studies is a core textbook for game studies as an academic discipline, and is the comprehensive guide to the field. It introduces the student to the history and character of games studies as an analytical study of games in culture, and then moves to provide an overview of games as signifying and dynamic cultural constructs. This book shows how to analyze games by introducing the core analytical concepts in the contexts of games and game cultures of four periods. It covers the prehistory of games, the 70s, 80s, and 90s and also contemporary developments. Students will be introduced to both the theoretical core and the essential genres and classics of the subject.